PREDIKTOR KECEMASAN PADA PASIEN CHRONIC KIDNEY DISEASE (CKD) DI RUMAH SAKIT PANTI RAPIH YOGYAKARTA - Fittriya Kristanti (Jurnal Ilmiah Keperawatan IMELDA, 2025)
Chronic Kidney Disease (CKD) has an impact on decreasing quality of life, increasing financial expenses and the most fatal condition, namely premature death. Hemodialysis is a therapy that can extend the life expectancy of CKD patients, but the Hemodialysis process has an impact on anxiety in CKD patients. The purpose of this study was to determine the predictors of anxiety in Chronic Kidney Disease patients in the Hemodialysis Room of Panti Rapih Hospital, Yogyakarta. The research design used was descriptive correlational and used a cross-sectional approach, with 33 respondents. The sampling technique was accidental sampling, this study was conducted in March 2023-April 2023 in the hemodialysis room of Panti Rapih Hospital, Yogyakarta. This study used the Hamilton Anxiety Rating Scale (HARS-A) and Multidimensional Scale of Perceived Social Support (MSPSS) instruments. The dependent variable in this study was anxiety, the independent variable was social support. The results showed that gender influenced anxiety in CKD patients undergoing HD therapy with a p value = 0.026. Predictors of anxiety in Chronic Kidney Disease patients in the Hemodialysis Room of Panti Rapih Hospital, Yogyakarta are education level and occupation.